A novel energy imbalance approach applied to rolling resistance assessment in cycling - Sellier, M.; Bellenoue, S. (Journal of Science and Cycling, 2025)
We present a novel approach for on-field rolling resistance testing, achieving repeatability below 2% using only 100-meter test sections. This method has been successfully applied to evaluate the influence of tire pressure, compare different tire versions within the same manufacturer, assess rolling resistance variations between manufacturers, and analyze the effect of tire temperature. Significant differences were observed, including a 26% increase in rolling resistance between 6 and 3 bar tire pressures, a 33% difference between Time-Trial and non-Time-Trial tire versions, a 9% average variation across three manufacturers, and a 26% increase between warm (18°C) and cold (14°C) tires.